Comparative Genomic Analyses Provide Insight Into the Pathogenicity of Metschnikowia bicuspidata LNES0119 - Jiang, Hongbo; Bao, Jie; Xing, Yuenan; Li, Xiaodong; Chen, Qijun (Frontiers in Microbiology, 2022)
Metschnikowia bicuspidata is a globally distributed pathogenic yeast with a wide range of aquatic hosts. A new strain, M. bicuspidata LNES0119, isolated from the Chinese mitten crab Eriocheir sinensis, has caused a serious reduction in production and marked economic loss for the aquaculture industry in China. Therefore, the whole-genome sequence of M. bicuspidata LNES0119 was sequenced using Illumina and Oxford Nanopore technology; whole-genome annotation and comparative genomic analyses of this pathogen were performed as well. A high-quality genome of M. bicuspidata LNES0119 was 16.13 Mb in size, with six scaffolds and six contigs, and encoded 5,567 putative predicted genes. Of these, 1,467 genes shared substantial homology with genes in the pathogen–host interactions database. Comparative genomic analyses of three M. bicuspidata strains and one non-pathogenic yeast, M. aff. pulcherrima, showed 331 unique genes in M. bicuspidata LNES0119, 30 of which were putatively related to pathogenicity. Overall, we identified several meaningful characteristics related to pathogenicity and virulence that may play essential roles in the infection and pathogenicity of M. bicuspidata LNES0119. Our study will aid in identifying potential targets for further exploration of the molecular basis of the pathogenicity of M. bicuspidata as well as the therapeutic intervention of M. bicuspidata infection.